Prophetic leadership and financial decision making quality: Partial Least Square (PLS) path modeling analysis. - Nik Maheran Nik Muhammad; Shahram Akbarzadeh (2012)
Prophetic leadership rests on the tenets of trait theory, spirituality, transcendent leadership and Religious leadership theory. It argues that leadership begins from within and works outward. Prophetic leadership also suggest the interconnectedness of leadership and social network theory, the necessity for finding common ground and synergy between leader and the followers and altruistic management to build leadership effectiveness. This paper proposed that prophetic leadership can be renewed by rethinking its theology and its epistemology across a full-spectrum of ‘Abrahamic faith’ prophets’ personality trait, organizational goal, task, and societal domains. It also analyzed the fitters of the model to financial sector via Partial Least Square (PLS) analysis using SmartPLS freely available software. Useable questionnaire of 110 respondents perceived that financial leaders hold the prophetic characteristics accept for posture and altruism. Financial decision qualities were derived from these characteristics.